The Application of Contextual Teaching and Learning (CTL) Method to Increase Motivation to Learn PPKN - Ari Budi Prihandoko (UM Purwokerto Press, 2025)
This study aims to identify the extent to which the application of Contextual Teaching and Learning (CTL) method can increase students' motivation and understanding of Pancasila values in learning Pancasila and Civics Education (PPKn) at SMK Negeri 1 Kaligondang. Based on the results of the pre-survey, it was found that most students had difficulty in understanding the basic concepts of the state and the practice of democracy. The CTL method is applied to connect the subject matter with the context of students' real life, so that learning becomes more relevant and applicable. This study used a Classroom Action Research (PTK) approach with 33 students as subjects and data collection through observation and questionnaires. The results showed that the application of the CTL method succeeded in increasing student motivation and activity, with an average increase in motivation of 82.9% in cycle II. It was also found that student and teacher activities experienced a significant increase in each cycle. This study concludes that the CTL method can improve the quality of Civics learning, especially in character building and understanding democratic values. Therefore, it is recommended for educators to continue applying CTL methods in learning to increase student participation and the relevance of the material being taught.